KONSEP INFAK DALAM AL-QUR’AN - Desri Ari Enghariano (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2020)
Al-Qur’an is guide (hudan) for human in general; both in the field of worship or in the field of muamalah. Currently the word is being hit by covid-19 which caused in economic crisis in various countries exposed to the virus, including Indonesia. And among the important concept in the qur’an that can be used as aguide to alleviate the economic crisis that hit the Indonesian country today is the concept of infak. It means distributing wealth whose purpose is to reach Allah’s reward. In simple language, it can be called by giving away property to another people, without expecting any compensation from the recipient. The infak is distributed to the needy, poor, dhuafa, and other people who need.